FORMATION OF VALUES IN ACTIVITIES OF THE FUTURE LAWYERS AND LAW ENFORCEMENT OFFICERS: HOW TO LEARN ETHICS WHILE STUDYING - Navickienė, Žaneta; Žilys, Vaidotas; Danišauskas, Gintautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article presents the relevance of values and steps for the formation of ethical principles for the future legal profession. The aim is focused on analysis of formation process of values for a lawyer and police by analyzing law and police study programs. The assessment scale of the public confidence in different law enforcement institutions (courts, the prosecutor's office, police, lawyers) shows that the society is watchful, indifferent and active evaluating the quality of law enforcement institutions as well as behavior of the officials. It means conceptual and consistent formation of values would ensure the efficiency of practical ethical model. Nine law and police study programs of higher schools in Lithuanian and four codes of professional ethics of law enforcement institutions were examined during the research. Also four lecturers were interviewed. The results of the research showed that in Lithuania the provisions of ethics are not taught in all higher schools preparing future lawyers and police officers. The provisions of professional ethics in different areas of lawyer's and police activities are clearly defined in codes of professional ethics as well as in recommendations applying these ethical provisions. However the pragmatic application of ethical provisions would be strengthened studying particular disciplines.